"Manipulation" of Crystal Structure by Methylthiolation Enabling Ultrahigh Mobility in a Pyrene‐Based Molecular Semiconductor. Issue 32 (5th July 2021) - Takimiya, Kazuo; Bulgarevich, Kirill; Abbas, Mamatimin; Horiuchi, Shingo; Ogaki, Takuya; Kawabata, Kohsuke; Ablat, Abduleziz
Abstract: Control and prediction of crystal structures of molecular semiconductors are considered challenging, yet they are crucial for rational design of superior molecular semiconductors. It is here reported that through methylthiolation, one can rationally control the crystal structure of pyrene derivatives as molecular semiconductors; 1, 6‐bis(methylthio)pyrene keeps a similar sandwich herringbone structure to that of parent pyrene, whereas 1, 3, 6, 8‐tetrakis(methylthio)pyrene (MT‐pyrene) takes a new type of brickwork structure. Such changes in these crystal structures are explained by the alteration of intermolecular interactions that are efficiently controlled by methylthiolation. Single crystals of MT‐pyrene are evaluated as the active semiconducting material in single‐crystal field‐effect transistors (SC‐FETs), which show extremely high mobility (32 cm 2 V −1 s −1 on average) operating at the drain and gate voltages of − 5 V. Moreover, the band‐like transport and very low trap density are experimentally confirmed for the MT‐pyrene SC‐FETs, testifying that the MT‐pyrene is among the best molecular semiconductors for the SC‐FET devices. Abstract : Methylthiolation is a simple but powerful way to control the crystal structures and thus the transport properties of molecular semiconductors; the sandwich herringbone structure of pyrene is altered into a new type of brickwork structure in 1, 3, 6, 8‐tetrakis(methylthio)pyrene (MT‐pyrene), which turns out to be an excellent molecular semiconductor showing ultrahigh mobility and band‐like transport in the single‐crystal field‐effect transistors.